2013
DOI: 10.1097/jce.0b013e3182a9045a
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiology and Autonomic Responses Perspective for Advancing Hybrid Brain-Computer Interface Systems

Abstract: The primary focus of this article was to review the current understanding of motor imagery (MI) as a cognitive process and thereby explore correlated biosignals for devising advanced brain-computer interfaces (BCIs) helping toward overcoming the limitations of current systems.To this end, the article first outlines the process of performing MI, ensuring kinesthetic experiences, and explores the literature to ascertain main brain areas that are activated during MI. Mental chronometry as a conventional method of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 166 publications
(275 reference statements)
0
1
0
Order By: Relevance
“…A brain-computer interface (BCI) is a system that translates human thoughts into an action via a control signal. Electroencephalogram (EEG) is the most widely used biological signal used for operating a BCI system since it has relatively short time constants and offers relatively high temporal resolution among noninvasive methods [ 1 3 ]. Numerous works over the past few decades have revealed that EEG signal recorded from the scalp are basis for BCIs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A brain-computer interface (BCI) is a system that translates human thoughts into an action via a control signal. Electroencephalogram (EEG) is the most widely used biological signal used for operating a BCI system since it has relatively short time constants and offers relatively high temporal resolution among noninvasive methods [ 1 3 ]. Numerous works over the past few decades have revealed that EEG signal recorded from the scalp are basis for BCIs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%